p-Cresyl Sulphate-Induced Osteoblast Activities Dysfunction and the Protective Roles of Eldecalcitol - Ahmad Faizal, Jelani (Universiti Malaysia Sarawak (UNIMAS), 2025)
p-Cresyl Sulphate (pCS), a uraemic toxin, has been implicated in the development of various bone abnormalities in chronic kidney disease (CKD) patients. However, the underlying mechanisms by which pCS induces these changes and the potential therapeutic strategies to mitigate its effects remain poorly understood. Eldecalcitol (ELD), an analogue of active vitamin D, is a drug used as a treatment of osteoporosis in Japan and China. However, it is unclear whether ELD can be used to manage diseases related to CKD. This study aimed to understand the mechanisms in which pCS affects the cell viability of human foetal osteoblast (hFOb 1.19) cells and its effects on the molecular pathways which could potentially lead to bone disorders such as osteoporosis. This study also aimed to explore the efficacy of ELD in preventing these alterations. Initially, the IC50 of pCS was determined, however the concentration proved to cause cell detachment and cell death. Instead, the IC30 of pCS and the non-toxic dose of ELD were first determined and used to investigate the molecular pathways involved in pCS-induced bone alterations and the protective effects of ELD. Then, oxidative stress was measured using a Reactive Oxygen Species (ROS) Assay Kit. Finally, Enzyme-Linked Immunosorbent Assay (ELISA) was performed to assess pCS-induced changes and subsequently the effect of ELD treatment on apoptotic markers and anti-apoptotic markers namely Caspase-8 (CASP-8), Caspase-9 (CASP-9), Caspase-12 (CASP-12), B-Cell Lymphoma-2 (BCL-2) and BCL-2 Associated X (BAX). Other markers investigated in this study included anti-oxidative markers [Superoxide Dismutase-3 (SOD-3), Glutathione Peroxidase-1 (GPX-1)], inflammatory markers [Interleukin-1β (IL-1β), Interleukin-6 (IL-6) and Tumour Necrosis Factor-α (TNF-α)] and bone markers [(Receptor Activator Nuclear Factor Kappa-B Ligand (RANKL), Osteoprotegerin (OPG), Osteopontin (OPN), Osteocalcin (OC), and Alkaline Phosphatase (ALP)] in pCS-exposed hFOb 1.19 cells. Our results demonstrated that 12 mM of pCS increased the expression of certain apoptotic markers (CASP-8, CASP-12, and BAX) and inflammatory markers (IL-1β and IL-6). Additionally, ROS was shown to be increased in a time dependent manner in the presence of pCS. Treatment with ELD at concentration between 0.25-1 µM resulted in the attenuation of CASP-8, IL-6 and IL-1β expression in pCS-exposed osteoblast. CASP-12 was shown to only be inhibited by lower concentrations of ELD (0.25 and 0.5 μM). All three concentrations of ELD were also shown to reduce the expression of SOD-3. Treatment with ELD at low and medium concentrations (0.25 and 0.5 μM) resulted in lower trend of ROS production compared to pCS group, although not statistically significant. Interestingly, treatment with high concentration of ELD (1 μM) produced an increasing trend of ROS production instead. Furthermore, ELD dose-dependently increased the expression of OC in pCS-exposed hFOb 1.19. No significant changes could be shown in the expression of markers CASP-9, BCL-2, GPX-1, RANKL, OPG, OPN, ALP and TNF-α with the addition of pCS and subsequent ELD treatment. In conclusion, this study has partially revealed the underlying cellular and molecular mechanisms that are altered by pCS in osteoblast and highlighted the potential of ELD as a therapeutic strategy to mitigate some of these alterations. Further investigation into the in-depth molecular pathways and long-term effects of ELD on bone health in the context of chronic kidney disease is warranted.